La antigua Roma y la ideología de la revolución norteamericana - García de Quevedo Rama, M.ª Diana (Gerión. Revista de Historia Antigua, 2005)
This article focuses on the understanding and use of ancient Rome, specially Republican Roma, by the American statesmen in the years of the emerging U.S.A. We deal with the role played by George Washington and Thomas Jefferson as transmitters of the Roman sources and ideas on dictatorship and democracy for the foundation of the American institutions. Finally, we analyse the way American slavery was excused on the basis of Roman slavery.